Analysis of Mineral Nutrition Status and Heavy Metal Contents in Selected Medical Plants used tn Traditional Treatments in Kyrgystan - ÖZYİĞİT, İBRAHİM İLKER (My University, 2022)
As the rest of the world, Kyrgyzstan suffers from the pollution in recent years as a result of urbanization following of economic and industrial development along with population growth. The negative effects of the pollution on organisms are observed all over the world. This is especially important for the plants consumed as food or medicinal purposes. Although the researches in many countries have been done on heavy metal pollution as well as on mineral nutrition statuses of herbs, similar researches performed in Kyrgyzstan have been limited. For this reason, this research comprising of elemental analysis of 90 different plant species used in three different Kyrgyz bazaars, namely Osh, Ortosai and Alamedin has been conducted in order to make estimation on the rate of pollution and the effects of pollution. One of the most important steps in inductively coupled plasma optical emission spectroscopy (ICP-OES) technology is sample preparation. For the parts of the each plant sample, 8 mL of 65% HNO3 was used using Teflon cell. The prepared samples were thawed in a Berghof –MSW2 microwave. The concentrations (in mg kg-1 ) of Al, B, Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb, and Zn in the dried samples have been determined by employing ICP- OES (PerkinElmer - Optima 7000DV). Although, the heavy metals determined in the medicinal plants have been found to be within the normal ranges, the allowable limits for some elements have been exceed. As observed: Al and Cu contents in Aconitum soongaricum, Urtica dioica and Eminium regelli; Cu and Fe contents in Antennaria dioica and Pastinaca sp.; Al and Fe contents in Cetraria islandica, Helianthus annuus, Chelidonium sp., Cichorium sp., Origanum vulgare, Ferula sp., Spongilla sp., Taraxacum sp. and Veronica sp.; Cd and Cu contents in Lemna sp. and Ferula sp.; Al, Cd and Fe contents in Salvia sclarea; Al, Cu and Fe contents in Viola sp. and Centaurea sp.; Al, Cd, Cu and Fe contents in Helichrysum arenarium; Al, Cu, Mn and Ni contents in Mentha piperita; and Al, Cu, Fe and Ni contents in Calendula sp. were found to be higher than normal limits. On the other hand, Cr and Pb contents were in acceptable ranges in all plants used. Heavy metals found in medicinal plants through food chain cause serious health problems in human. Therefore, safe and high quality consumption of herbs can be only provided by conducting comprehensive analyzes during the production processes of herbal goods. Medicinal plants contain important essential elements involved in metabolic processes; however, containing high concentrations of these elements also lead to medical problems. Hence, it is of great importance to determine the accumulation rates of minerals in medicinal plants. Finally, identification of possible contamination factors in the food chain (from the field to humans) is important to take the necessary precautions for the safe production. Keywords: Bishkek, Ethnobotany, Heavy metals, Medicinal plants, Nutrient elements
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; Bishkek; Ethnobotany; Heavy metals; Medicinal plants; Nutrient elements